Validation of alkoxysilane-based protective treatments for increasing service life of cementitious materials under different weathering conditions - Rafael Zarzuela; Manuel Luna; Giada Gemelli; Jorge Gonzalez-Coneo; Inés García-Lodeiro; M.T. Blanco-Varela; María J. Mosquera (Developments in the Built Environment, 2023)
Gradual degradation of cementitious materials by exposure to the environment decreases the lifespan of buildings, increasing maintenance andrepair costs. Surface treatments based on alkoxysilanes may prevent weathering effects and repair onset damages, though little attention is paid to how the physical-chemical alterations caused by weathering affect their performance.This work reports a comprehensive characterization/validation of an alkoxysilane-based protective treatment on a mortar subjected to different artificial aging processes (freeze-thaw, thermal cycles, carbonation and chlorides), including measurements of water transport, mechanical properties, reaction products and durability under freeze-thaw and sulfate exposure cycles.Formation of compact silica and C-S-H gel structures decreases porosity and water absorption rate with minimal effect on vapor permeability. Bulk mechanical reinforcement and waterproofing are substantially limited on freeze-thaw aged mortars, whereas surface hardness is barely increased for carbonated mortars. These properties were found to effectively increase the mortar resistance against sulfate and freeze-thaw induced damages.